SISTEM INFORMASI PENERIMA BANTUAN BIBIT IKAN PADA BALAI BENIH IKAN (BBI) KECAMATAN RANTAU KOPAR - Erliza Yubarda; Rini Rahayu (AMIK Mitra Gama, 2019)
Abstract Fish Seed Center is a means of government in distributing fish seeds to the public free of charge which in processing data fish recipients still use conventional systems by recording the ledger, where the books are easily damaged so that the processing of data is still not effective and efficient. This makes it difficult to get accurate information and data if needed at any time. Answering these problems, the Data Processing Information System designed for Fish Seed Aid Recipients at the Fish Seed Center (BBI) of Rantau Kopar District uses the Visual Basic.Net Programming Language and Mysql Database to facilitate employee parts in processing data and making reports. So that it can provide accurate and accurate information in the data search process. Applications are made including data on fish seed recipients, fish seed data, and data requirements fulfilled by fish seed aid recipients and reports relating to the object of research. The results of system testing obtained include reducing the risk of data duplication and data loss. Keywords : Recipient, Help, Fish Seeds, Visual Basic.Net, MySQL.